Parathyroid hormone alters collagen synthesis and procollagen mRNA levels in fetal rat calvaria. - Kream, B E (1980)
Parathyroid hormone decreased the incorporation of [3H]proline into collagenase-digestible protein in cultured 21-day fetal rat calvaria but had little effect on the labeling of noncollagen protein. After 24 hr of culture, there was a 50% reduction in collaghen synthesis and a 40% decrease in the level of functional procollagen mRNA as measured in a reticulocyte lystate translation assay. The effect of parathyroid hormone on both parameters was detectable after 6 hr of treatment. In these cultures, there was also a substantial degradation or release of newly synthesized collagen from the calvaria, but parathyroid hormone had little effect on the release of collagen into the medium. These results suggest that parathyroid hormone inhibits collagen synthesis primarily by decreasing the steady-state level of procollagen mRNA.